Regional Taxes and Retributions as a Source of Fixed Regional Income Every Year - Permana Putra, Athaya Faris; Murti, Galuh Tresna; Fitrian, Haura Muthi; Putri, Raisha Mellyani (INVOICE : JURNAL ILMU AKUNTANSI, 2023)
One of the main objectives of Regional Taxes and Regional Levies is to determine the level of effectiveness achieved for each type of tax, the effect of local tax revenue on the contribution of each type of regional tax (PAD), and people's welfare. in the city of Bandung. The problems faced by regions in general are exploring sources of regional taxes and regional fees which are one of the PAD components, which have not contributed significantly to regional revenues as a whole. Through the secondary data research method the author tries to answer the above problems in this thesis by examining PAD components which have not made a significant contribution.